Biological activities of locally isolated thermophilic fungi - Al-Bajalany, Laith Yaseen Arif (2015)
Fungi are organisms of great interest in fermentation processes that culminate in the production of secondary metabolites important in research for new antibiotics, anticancer agents, insecticides, herbicides and others. The discovery and development of antibiotics was one of the most significant medical advances in the twentieth century. Recent researcher trends showed that the discovery of active chemical compounds is to update the effectiveness of drugs that are used in the future, so that, it is necessary to screen new isolated fungi to identify new antimicrobial bioactive compounds. Hence, this research was aimed to study new producers of secondary metabolites from thermophilic fungi and determined their biological properties. Ten thermophilic fungi were chosen out of 30 species isolated locally from Peninsular Malaysia. The investigations of the extracts demonstrated the availability of phenolics (14.61) to (19.64) mg gallic acid equivalenUg which analysed by high performance liquid chromatography (HPLC) and demonstrated the availability of 10 phenolics; pyrogallol, syringic acid, gallic acid, cinnamic acid, salicylic acid, chlorogenic acid, resorcinol, vanillic acid, caffeic acid, and hypophyllanthin, and furthermore the 4 flavonoids (apigenin, daidzein, catechin, and epicatechin). Other 14 fundamental metabolites located by GC-MS included: acetic acid 20.81 %, 2,3-Butanediol 42.92%, 2-Furoic acid hydrazide 16.79%, cis-9-Hexadecenoic acid (palmitoleic acid) 10.07%, lsosorbide 5.23%, 9-Octadecenoic acid, methyl ester, (E)- (oleic acid) 22.08%, cis-Vaccenic acid (cis-11-Octadecenoic acid) 13.03%, 1-Naphthalenol, 1,2,3,4-tetrahydro-2,5,8- trimethyl- 9.92%, .alpha.-D-Glucopyranoside, methyl 19.03%, 3,5-Dihydroxy-6- methyl-2,3-dihydro-4H-pyran-4-one 5.27%, 2-Furoic acid, methyl ester 8.76%, Niacinamide 7.75%, 9, 12-Octadecadienoic acid, methyl ester (Linoleic acid methyl ester) 4.26% and Pentadecanecarboxylic acid (palmitic acid) 6.78% from all the ten fungal isolates. All methanolic extracts of thermophilic fungi demonstrated a range of antimicrobial activities against both Gram positive and Gram negative pathogenic microorganisms (Inhibition zone: 6.3mm to 25.7mm) at the concentrations of 250, 500 and 1000 μg/disc. Extracts displayed antioxidant activities had a tendency to scavenge the free radicals in the decrease of ferric ion (Fe3•) to ferrous ion (Fe2•) FRAP (50.97 to 79.1 %), DPPH (50.62 to 57.48%), ABTS (50.41 to 62.51 %) and NO (51.17 to 59.45%) for all the isolates. Cytotoxicity results demonstrated the capability of methanol extracts from Myce/iopthora thermophila as a source of anticancer therapeutic agents to breast cancer cells MCF-7 at an IC50 concentration of 29.97μg/ml with cell viability 36.66% and cytotoxicity 90.18% against MDBK cell line. For the thermophilic fungus Myceliophthora thermophi/a, the extract concentrate inhibited 50.43% of the inducible nitric oxide synthase in a measurements dose dependent manner at 250μg mL- 1, while kept up 91.13% of macrophage RAW 264.7 cell lines induced by LPS/IFN-y demonstrating their obvious anti-inflammatory activity.